An Italian Multicenter Study on the Epidemiology of Respiratory Syncytial Virus During SARS-CoV-2 Pandemic in Hospitalized Children - Nenna, Raffaella; Matera, Luigi; Licari, Amelia; Manti, Sara; Di Bella, Gaia; Pierangeli, Alessandra; Palamara, Anna Teresa; Nosetti, Luana; Leonardi, Salvatore; Marseglia, Gian Luigi; Midulla, Fabio; , ICHRIS Group; et al. (Frontiers in Pediatrics, 2022)
Since the beginning of 2020, a remarkably low incidence of respiratory viruses’ hospitalizations has been reported worldwide. We prospectively evaluated 587 children, aged < 12 years, admitted for respiratory tract infections from September 1, 2021 to March 15, 2022 in four Italian pediatric hospitals to assess the burden of respiratory viruses during COVID-19 pandemic in Italy. At admission, a Clinical Respiratory Score was assigned and nasopharyngeal or nasal washing samples were collected and tested for respiratory viruses. Total admissions increased from the second half of October 2021 to the first half of December 2021 with a peak in early November 2021. Respiratory syncytial virus (RSV) incidence curve coincided with the total hospitalizations curve, occurred earlier than in the pre-pandemic years and showed an opposite trend with respect to the incidence rate of SARS-CoV-2. Our results demonstrated an early peak of pediatric hospitalizations for RSV. SARS-CoV-2 may exhibit a competitive pressure on other respiratory viruses, most notably RSV.